Use of hydrocolloid protective sheets to protect skin against direct contact from body secretions - Nur Madalinah Tan, & Josephine Ong, & Feng Ying, & Ong Ling and & Catherine Loo & (WCET Journal - Spanish Edition, 2021)
Hydrocolloid protective sheets provide a moist favourable environment for wound healing and act as a barrier against exogenous bacteria. They do not adhere to the wound, only to the surrounding skin, and can provide more a more rapid wound healing environment, keeping newly healed skin intact and preventing breakdown of tissue. Hydrocolloid protective sheets do not traumatise the skin upon removal, reducing pain, and require fewer dressing changes as they may be left in place for several days at a time. They come in different sizes which can be custom-cut to fit the wound. Their use can also reduce the cost of care, length of stay in hospital and amount of care rendered by WOC nurses. The three case studies in this article describe how stomal therapy nurses approached the nursing management of denuded skin using hydrocolloid protective sheets on peristomal skin, the buttocks and perineal regions.